Electrophysiological evaluation of the neuromuscular junction: a brief review - Kouyoumdjian, João Aris; Estephan, Eduardo de Paula (Arquivos de Neuro-Psiquiatria, 2023)
The nerve terminal and muscle membrane compose the neuromuscular junction. After opening the voltage-gated calcium channels, action potentials from the motor axons provoke a cascade for the acetylcholine release from synaptic vesicles to the synaptic cleft, where it binds to its receptor at the muscle membrane for depolarization. Low amplitude compound muscle action potential typically presents in presynaptic disorders, increasing by more than 100% after a 10-second effort in the Lambert-Eaton myasthenic syndrome and less in botulism. Needle electromyography may show myopathic motor unit action potentials and morphological instability (“jiggle”) due to impulse blocking. Low-frequency repetitive nerve stimulation (RNS) is helpful in postsynaptic disorders, such as myasthenia gravis and most congenital myasthenic syndromes, where the number of functioning acetylcholine receptors is reduced. Low-frequency RNS with a decrement >10% is abnormal when comparing the 4th to the first compound muscle action potential amplitude. High-frequency RNS is helpful in presynaptic disorders like Lambert-Eaton myasthenic syndrome, botulism, and some rare congenital myasthenic syndromes. The high-frequency RNS releases more calcium, increasing the acetylcholine with a compound muscle action potential increment. Concentric needle records apparent single-fiber action potentials (spikes). A voluntary activation measures the jitter between spikes from two endplates. An electrical activation measures the jitter of one spike (one endplate). The jitter is the most sensitive test for detecting a neuromuscular junction dysfunction. Most neuromuscular junction disorders are responsive to treatment.
Keywords: Neuromuscular Junction; Myasthenia Gravis; Repetitive Nerve Stimulation; Single-Fiber Electromyography; Jitter